BEBERAPA FAKTOR YANG MEMPENGARUHI PRICE EARNINGS RATIO STUDI PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TELAH GO-PUBLIC DI BURSA EFEK INDONESIA - Purba, Saut (UNIKA Santo Thomas, 2015)
This study aims: First, to get the variables that affect the price earnings ratio. Second, to obtain empirical evidence about the impact of these variables on price earnings ratio. To achieve this purpose, research on companies listed on the Indonesia Stock Exchange at the end of 2013. The number of companies manufacturing the research samples as many as 98 companies. By using eight regression model to explain the determinants of price-earnings ratio is obtained the following results. First, return on equity, the expected yield or capitalization rate, growth, dividend payout ratio, total asset turnover, net profit margin, and the debt to equity ratio is a determinant of price-earnings ratio. Second, the return on equity have a positive influence and significant impact on the price earnings ratio, expected returns or the capitalization rate affects negatively and significantly influence on the price earnings ratio, growth positive influence and significant impact on the price earnings ratio, dividend payout ratio positive effect and significant to price earnings ratio, total asset turnover and significant positive effect on the price-earnings ratio, net profit margin and significant positive effect on the price-earnings ratio, and debt to equity ratio and significant positive effect on the price earnings ratio. Third, the debt to equity ratio is the dominant determinant of the price earnings ratio. Fourth, the price earnings ratio variation able to be explained by variations in the independent variables of 43.1 to 75.6 percent. It may therefore be argued that this study is useful for: First, to provide information to investors about the variables that need to be considered when investing in the stock market and affect the price earnings ratio. These variables are the retention ratio, dividend payout ratio, total asset turnover, net profit margin, debt to equity ratio, the required yield, growth, and return on equity. Second, add a reference to the capital market in relation to fundamental factors. Third, the results of this study are expected to be a reference to the head of the company in order to increase the value of the company.